Multipoint problem for typeless systems of differential equations with constant coefficients - Ptashnik, B. I.; Sylyuha, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For typeless systems of differential equations with constant coefficients, we investigate the well-posedness of the problem with multipoint conditions for a selected variable and 2π-periodic conditions for the other coordinates. The conditions of univalent solvability are established and the metric theorems are proved for lower bounds of small denominators that appear in the construction of solutions of the problems.